POVERTY ALLEVIATION IN INDONESIA DURING THE COVID-19 PERIOD 2019-2022: SYSTEMATIC LITERATURE REVIEW WITH VOS VIEWERS BIBLIOMETRICS - Dina Arfianti Siregar; Zuhrinal M Nawawi; Isnaini Harahap (Jurnal Ekonomi, 2023)
Poverty is a multidimensional problem because it is related to the inability to access economically, socio-culturally, politically and participate in society. The forms of poverty that exist in Indonesia and the various factors that cause them, of course, greatly influence the policy formulation that is made. This research was conducted by analyzing 20 of the 420 articles searched through the Publish or Perish application from 2019-2022 from selected literature discussing poverty using the publication name "Journal" and the keywords "Poverty", "Income" and Covid "19 ”. The results of this research are mapped using the VOSViewers with network visualization maps of research developments around poverty and income during Covid 19 using the VOSViewers Bibliometric Study of 5 clusters and 39 topics. The author simplifies the topic with novelty which we will discuss on this topic by taking samples, namely poverty alleviation. Poverty alleviation during the Covid-19 period 2019-2022 from observations can be carried out by means of agricultural development, human resource development, the role of non-governmental organizations. Working, Helping Weak Families, and Alleviating Poverty with Zakat